A German-language replication study analysing the role of figurative speech in reasoning - Christmann, Ursula; Göhring, Anne-Louise (Scientific data, 2016)
According to the metaphorical framing model, the use of metaphors in discussing an issue influences recipients’ understanding and assessment of that issue. In a recent study, participants read a text referring to a city’s crime problem either as a beast or a virus and then proposed counter-measures for that problem. Participants’ suggestions differed depending on the metaphor they had read. This replication matched the original procedure regarding the content of the rhetorical figures ( beast vs virus ), the topic under focus (crime) and the measurement of the dependent variable (open-end format to collect participants’ proposals). The procedure differed from the original with respect to language (German instead of English) and by including the formal type of rhetorical figure (metaphor or simile) as a factor. A systematic influence of the content of the figure on subjects’ proposals was observed. Presenting the rhetorical figure as a metaphor or a simile had no effect. Taken together, we were able to replicate the main effect of the original study. Metaphors do indeed frame reasoning. Design Type(s) 2x2 factorial design Measurement Type(s) inductive reasoning Technology Type(s) questionnaire Factor Type(s) experimental condition Sample Characteristic(s) Homo sapiens Machine-accessible metadata file describing the reported data (ISA-Tab format)